2019
DOI: 10.1111/jth.14398
|View full text |Cite
|
Sign up to set email alerts
|

Direct oral anticoagulants in patients with venous thromboembolism and thrombophilia: a systematic review and meta‐analysis

Abstract: We investigated direct oral anticoagulant (DOAC) use in venous thromboembolism and thrombophilia. A comprehensive search identified 10 studies, 8 of which were included in a meta‐analysis. DOACs were overall safe and effective in patients with venous thromboembolism and thrombophilia. Efficacy/safety of DOACs was maintained in low‐risk antiphospholipid syndrome patient subgroup. Summary BackgroundDirect oral anticoagulants (DOACs) are increasingly used in acute and long‐term treatment of venous thromboembol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 64 publications
3
82
0
2
Order By: Relevance
“…1, panel D). In a systematic review by Elsebaie et al, including mostly patients with factor V Leiden mutation and antiphospholipid antibodies, the risk reduction for thrombosis recurrence with anti-IIa vs VKAs (RR, 0.50; 95% CI, 0.19 to 1.34) appeared greater than that observed for anti-Xa vs VKAs (RR, 1.02; 95% CI, 0.35 to 2.97), although not statistically significant [10]. Although not definitive, these results open the possibility that certain patients with CT may derive better protection from thrombosis with specific agents.…”
Section: Pathophysiology Of Thrombosis Risk In Ct -Theoretical Interamentioning
confidence: 87%
“…1, panel D). In a systematic review by Elsebaie et al, including mostly patients with factor V Leiden mutation and antiphospholipid antibodies, the risk reduction for thrombosis recurrence with anti-IIa vs VKAs (RR, 0.50; 95% CI, 0.19 to 1.34) appeared greater than that observed for anti-Xa vs VKAs (RR, 1.02; 95% CI, 0.35 to 2.97), although not statistically significant [10]. Although not definitive, these results open the possibility that certain patients with CT may derive better protection from thrombosis with specific agents.…”
Section: Pathophysiology Of Thrombosis Risk In Ct -Theoretical Interamentioning
confidence: 87%
“…Experience of DOACs or LMWH in severe PC deficiency is restricted to single case reports . The use of selective direct inhibitors of FIIa or FXa in other severe prothrombotic disorders such as antiphospholipid syndrome remains controversial because of incomplete efficacy in some studies …”
Section: Introductionmentioning
confidence: 99%
“…14 There are limited data describing the efficacy and safety of DOACs in rare heritable thrombophilias such as PC deficiency. 15 In a subgroup analysis of patients with mild PC deficiency with VTE in the RE-MEDY trial, the FIIa inhibitor dabigatran was noninferior to VKA for preventing recurrent VTE. 16 Similarly, in the EINSTEIN-DVT, EINSTEIN-PE and Hokusai-VTE trials, [17][18][19] a subgroup meta-analysis showed no difference in efficacy between the FXa inhibitors rivaroxaban or edoxaban, and VKA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations